2014
DOI: 10.1097/mph.0b013e31828e54a5
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes in Patients With Mixed Phenotype Acute Leukemia in Morocco

Abstract: Mixed phenotype acute leukemia (MPAL) includes biphenotypic and bilineal types of leukemia, which constitute rare subtypes that require individualized therapy. Outcomes in Moroccan patients with MPAL are unknown. Among 1264 patients with acute leukemia, 20 were classified as having MPAL, including 17 with biphenotypic acute leukemia (1.3%) and 3 with bilineal leukemia (0.2%). There were 8 adults and 12 children. In 12 cases (60%), leukemic blasts expressed myeloid and T-lymphoid antigens, and, in 5 cases (25%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…Our results also showed a high incidence of Philadelphia chromosome positive (21.6%) or BCR-ABL translocation (20.6%) in MPAL, which was consistent with the report by Atfy et al [ 13 ]. As reported by Matutes et al [ 12 ] and Bachir et al [ 14 ], we also observed a high incidence of cytogenetic abnormalities in MPAL with only a small number of the cases displaying a normal karyotype.…”
Section: Discussionsupporting
confidence: 87%
“…Our results also showed a high incidence of Philadelphia chromosome positive (21.6%) or BCR-ABL translocation (20.6%) in MPAL, which was consistent with the report by Atfy et al [ 13 ]. As reported by Matutes et al [ 12 ] and Bachir et al [ 14 ], we also observed a high incidence of cytogenetic abnormalities in MPAL with only a small number of the cases displaying a normal karyotype.…”
Section: Discussionsupporting
confidence: 87%
“…The COG MPAL cohort described here, the iBFM AMBI2012 registry study, and the few pediatric case series for MPAL all suggest that beginning with ALL therapy results in similar or greater OS in comparison with AML regimens. A recent meta‐analysis of patients with MPAL also reported a survival benefit from starting with ALL therapy, although patient‐level data revealed equivalent OS with AML therapy .…”
Section: Discussionmentioning
confidence: 72%
“…Because of the rarity of pediatric MPAL, reports limited to children and adolescents are sparse . Similarly to the AMBI2012 registry, the strength of the cohort presented here is the use of a central review of immunophenotyping, which was supplemented as necessary with additional characterization from residual banked samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most cases of acute leukemias (AL) can be assigned a specific differentiation along a single lineage according to morphology, cytochemistry, comprehensive panel of immunological markers karyotyping, and molecular genetic analyses. However, there are uncommon cases of patients with AL having immunophenotypic feature characteristics of >1 cell lineage without any specific genetic aberrations contributing to myeloid or lymphoid phenotypes 1‐3 …”
Section: Introductionmentioning
confidence: 99%